2018
DOI: 10.1016/j.seizure.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of deviation from treatment guidelines in status epilepticus: A systematic review

Abstract: This review provides preliminary evidence that non-adherence to SE guidelines negatively impacts on patient outcomes. Appropriate and timely treatment is imperative for rapid seizure termination and improving outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 34 publications
3
36
0
1
Order By: Relevance
“…Inadequate dosing and overuse of benzodiazepines leading to respiratory failure and intubation, and a delay to second-line therapy have previously been highlighted. 11 Second-line treatment of established SE was essentially evenly split evenly between phenytoin and levetiracetam in this survey, which reflects the current literature, with the trend towards the newer and easier to us levetiracetam, which has been recently shown to be non-inferior to phenytoin in both children and adults. [23][24][25] Levetiracetam treatment failure in the past may have been attributable to significant underdosing.…”
Section: Management Of Sesupporting
confidence: 74%
See 1 more Smart Citation
“…Inadequate dosing and overuse of benzodiazepines leading to respiratory failure and intubation, and a delay to second-line therapy have previously been highlighted. 11 Second-line treatment of established SE was essentially evenly split evenly between phenytoin and levetiracetam in this survey, which reflects the current literature, with the trend towards the newer and easier to us levetiracetam, which has been recently shown to be non-inferior to phenytoin in both children and adults. [23][24][25] Levetiracetam treatment failure in the past may have been attributable to significant underdosing.…”
Section: Management Of Sesupporting
confidence: 74%
“…10 A recent systematic review from Australian authors concluded that there are often deviations from published within hospital guidelines of SE, and that non-adherence to these guidelines is associated with worse outcomes. 11 Significantly improved outcomes in seizure cessation, necessity for ICU admission and length of stay, have been demonstrated with adherence to treatment protocols. 12 While neurologists and epileptologists may not always be involved in the initial management of CSE, their input is invariably needed in NCSE; thus, their involvement in the development of treatment guidelines and use of cEEG is required.…”
Section: Introductionmentioning
confidence: 99%
“…Our compliance rate of 3% compared with the published literature, where adherence rates to guidelines ranged from 14.3% to 66% . A recent systematic review shows poor outcomes, including increased intubation, following deviation of guidelines …”
Section: Discussionmentioning
confidence: 99%
“…9 A recent systematic review shows poor outcomes, including increased intubation, following deviation of guidelines. 10 Age and aetiology have been shown to be the main predictive factors for SE outcome. 11,12 However, there are limited data regarding adherence to guidelines and the outcomes of SE.…”
Section: Compliance To Management Guidelinesmentioning
confidence: 99%
“…Previous studies have evaluated the association between adherence to status epilepticus guidelines and clinical outcomes, with controversial results. 38,39 Standardization of short and long-term clinical outcomes may guide our understanding on the importance of guideline adherence in the treatment of status epilepticus and the need of strategies to improve adherence. Second, although we have examined our pathways during a contemporary time period (between August 2016 and August 2017), these pathways are constantly evolving.…”
Section: Aed Dosesmentioning
confidence: 99%